A novel isogeometric analysis enriched element for a V-notched one-dimensional hexagonal piezoelectric quasicrystal bi-material. (October 2021) - Yang, Zhenting; Yu, Xiong; Tong, Zhenzhen; Xu, Chenghui; Zhou, Zhenhuan; Xu, Xinsheng
Highlights: A novel enriched element is proposed for fracture analysis of notched PQC bi-material. Analytical symplectic eigensolutions are introduced to enhance the accuracy of the IGA. Analytical notch intensity factors and multi-physical fields are obtained simultaneously. Effects of sustained angles and positions of notches on the singularities are investigated. Abstract: A novel isogeometric analysis enriched element for accurate evaluation of singularities arising at the interface in V-notched one-dimensional hexagonal piezoelectric quasicrystals (PQCs) under anti-plane loading is developed. By taking the advantages of IGA and symplectic methodology, an enriched element centered at the notch tip is constructed by analytical symplectic eigensolutions. Explicit expressions of notch intensity factors and singular multi-physical fields within enriched element are obtained simultaneously. A comparison study between numerical predictions and analytical solutions is performed and excellent agreements are observed. Furthermore, the notch intensity factors for different V-notched PQC bi-material are presented and discussed in detail.